Papel da eritropoetina recombinante humana sobre o metabolismo dos carboidratos, paratormônio, cálcio iônico, zinco, prolactina e níveis pressóricos em renais crônicos tratados com hemodiálise - Balbi, André Luis [UNESP]; Barretti, Pasqual [UNESP]; Da Silva Franco, Roberte Jorge [UNESP] (My University, 2006)
Objective: To evaluate the influence of recombinant human erythropoietin (Epho) on carbohydrate metabolism, parathyroid hormone, calcium ionic, zinc, prolactin and blood pressure (BP) in chronic renal failure treated by hemodialysis. Methods: Ten patients in hemodialysis were followed during 24 weeks in two phases: 12 weeks pre-Epho (BP was measured pre and post hemodialysis sessions) and 12 weeks post-Epho (BP was measured as above and also the blood levels of glucose, insulin, parathyroid hormone, calcium ionic, prolactin, and zinc). Results: Patients were 39.8±8.5 y, 50% males. Hematocrit and hemoglobin presented a significant increase four weeks after Epho (22.3±2.3 to 28.1±2.6% and 7.4±0.8 to 9.4±0.9 g/dL, p<0.05). BP (mmHg) and weight pre-Epho: 158±99 and 59±13 (before hemodialysis), 147±96 and 55±13 (after hemo) and post-Epho: 161±100 and 59±13 (before hemo) 155±101 and 56±12 (after hemo) were all not statistically different in any moment. There are also no difference pre and post-Epho in fast glucose (91.8±6.5 and 90.8±6.1 mg/dL, p>0.05), parathyroid hormone (341.4±249.3 and 515.7±310 pg/ mL), calcium ionic (3,66±0.63 and 3.76±0.45 mmol/L), prolactin (males: 327±144.1 and 298.1 ±145.2 μg/mL; females: 666.2±426.6 and 659±395.3 μg/mL) and zinc (median of 0.73 and 0.71 μg\L). Basal insulin was lower after Epho (median of 9.1 to 3.8 μg/mL, p<0.05). Conclusion: These data suggest that recombinant human erythropoietin was effective to improve the anemia and the carbohydrate metabolism in patients with chronic renal failure treated by hemodialysis. © Copyright Moreira Jr. Editors. Todos os direitos reservados.
Role of recombinant human erythropoietin on carbohydrate metabolism, parathyroid hormone, calcium ionic, zinc, prolactin and blood pressure in chronic renal failure treated by hemodialysis
Keywords: Anemia; Blood pressure; Chronic renal failure; Hemodialysis; Insulin; Recombinant human erythropoietin; calcium ion; erythropoietin; glucose; hemoglobin; insulin; parathyroid hormone; prolactin; adult; blood pressure; calcium blood level; chronic kidney failure; clinical article; glucose blood level; hematocrit; hemodialysis; human; insulin blood level; prolactin blood level; zinc blood level